Thermal annealing as an easy tool for the controlled arrangement of gold nanoparticles in block-copolymer thin films - Ledo Suárez, Ana (2013)
The results indicated that all three blends used as modifiers (PSn/PSnSH@Au) were successfully located in the PS phase during thermally induced BC self-assembly for a composition range from 5 to 43 wt% without macro-phase separation. The PSnSH@Au moiety experienced molecular desorption, nanocrystal core coalescence and partial molecular re-encapsulation processes during thermal annealing, leading to sphere-like gold NPs with a larger average size (without exceeding an interdomain distance). Ligand chain length regulated the degree of coalescence and re-encapsulation, defining ultimate core size. Furthermore, proper combination of chain length and composition enabled tuning of NP partitioning and arrangement on different length scales through thermally activated cooperative assembly processes. These results have not only significant impact for establishing thermal processing as a useful tool for the precise control of NP size and distribution, but also much broader implications for many nanoparticle-based technologies.